Treatment of hypertension during pregnancy: a cohort of pregnancy episodes from the SIDIAP database, Catalonia, Spain - Gomez-Lumbreras, Ainhoa; Vilaplana-Carnerero, Carles; Lestón Vázquez, Marta; Vedia, Cristina; Morros, Rosa; Giner-Soriano, Maria (Frontiers in Pharmacology, 2024)
Background: Hypertension during pregnancy is one of the most frequent causes of maternal and fetal morbimortality. Perinatal and maternal death and disability rates have decreased a 30%, but hypertension during pregnancy has increased around 10% in the last 30 years. This research aimed to describe the pharmacological treatment and pregnancy outcomes of pregnancies with hypertension.Methods: observational cohort study from the Information System for the Development of Research in Primary Care (SIDIAP) database. Pregnancy episodes with hypertension (ICD-10 codes for hypertension, I10-I15 and O10-O16) were identified. Antihypertensives were classified according to the ATC WHO classification: β-blocking agents (BB), calcium-channel blockers (CCB), agents acting on the reninangiotensin system (RAS agents), diuretics and, antiadrenergic agents. Exposure was defined for hypertension pregnancies with ≥2 prescriptions during the pregnancy episode. Descriptive statistics for diagnoses and treatments were calculated.Results: 4,839 pregnancies with hypertension diagnosis formed the study cohort. There were 1,944 (40.2%) pregnancies exposed to an antihypertensive medication. There were differences in mother's age, BMI, and alcohol intake between pregnancies exposed to antihypertensive medications and not exposed.BB were the most used (n=1,160 pregnancy episodes; 59.7%) followed by RAS agents (n=825, 42.4%), and CCB were the less used (n=347, 17.8%).Pregnancies with hypertension were exposed to antihypertensive medications, mostly BB. We plan to conduct a study focus on the RAS agents use during pregnancy and its outcomes in the offspring.